2022
DOI: 10.1108/lodj-07-2021-0349
|View full text |Cite
|
Sign up to set email alerts
|

Innovative culture and rewards-recognition matter in linking transformational leadership to workplace digitalisation?

Abstract: PurposeThis paper aims to examine the mediating effect of innovative culture in the relationship between transformational leadership and workplace digitalisation; and the moderating effect of rewards and recognition on the transformational leadership–innovative culture relationship.Design/methodology/approachA total of 256 valid samples were used in the structural equation modeling tests. The respondents were management-level executives from companies in Selangor/Kuala Lumpur, Malaysia.FindingsThe findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
0
0
1
Order By: Relevance
“…(Rai et al, 2018). (Hooi & Chan, 2022) Tentukan apakah manfaat yang Anda terima dengan mengikuti kontes bersifat nyata atau nontradisional (seperti bonus, tunjangan, kenaikan gaji, dan pujian) persyaratan yang lebih panjang dan baru (misalnya kesejahteraan fisik dan emosional karyawan). Karyawan merasa dihargai ketika mereka dihargai atas usaha mereka.…”
Section: Rewards and Recognitionunclassified
“…(Rai et al, 2018). (Hooi & Chan, 2022) Tentukan apakah manfaat yang Anda terima dengan mengikuti kontes bersifat nyata atau nontradisional (seperti bonus, tunjangan, kenaikan gaji, dan pujian) persyaratan yang lebih panjang dan baru (misalnya kesejahteraan fisik dan emosional karyawan). Karyawan merasa dihargai ketika mereka dihargai atas usaha mereka.…”
Section: Rewards and Recognitionunclassified
“…This research represents one of the earliest investigations into the role of information literacy and digital literacy as novel antecedents of technology acceptance models in the workplace. (Hooi & Chan, 2022) A study found that the connection between transformational leadership and workplace digitalization is influenced by an innovative culture. Furthermore, awards and recognition play a moderating role in the relationship between transformational leadership and an innovative culture.…”
Section: Introduce the Problemmentioning
confidence: 99%
“…. Innovative behavior refers to the ability of individuals to generate and implement new ideas and solutions (Hooi & Chan, 2022). This can involve creating new goods or services, discovering more effective methods of operation, or coming up with creative answers to challenging issues.…”
Section: Introductionmentioning
confidence: 99%
“…IT staff members that exhibit innovative work behavior can assist their firms in staying on top of the latest developments in technology and market trends. They can also aid in streamlining procedures, boosting productivity, and boosting client happiness (Erhan et al, 2022;Hooi & Chan, 2022;Rafique et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation